2013
DOI: 10.1161/strokeaha.111.680256
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Blockade During Sinusoidal Baroreflex Activation Proves Sympathetic Modulation of Cerebral Blood Flow Velocity

Abstract: Baroreceptor stimulation by means of sinusoidal neck suction (NS) at 6 and 12 cycles per minute, that is, at 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…HG maneuver alone increased variability, whereas HDT + HG did not alter MAP variability in the LF range (Table 2). Human and animal studies have shown that arterial blood pressure variability in the LF range is related to the sympathetic activity (Pagani et al 1986;Hilz et al 2013). Our results indicate an increase in the sympathetic activity during HG alone compared to rest (increased MAP variability, Table 2).…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…HG maneuver alone increased variability, whereas HDT + HG did not alter MAP variability in the LF range (Table 2). Human and animal studies have shown that arterial blood pressure variability in the LF range is related to the sympathetic activity (Pagani et al 1986;Hilz et al 2013). Our results indicate an increase in the sympathetic activity during HG alone compared to rest (increased MAP variability, Table 2).…”
Section: Discussionsupporting
confidence: 49%
“…; Hilz et al. ). Our results indicate an increase in the sympathetic activity during HG alone compared to rest (increased MAP variability, Table ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations